Synthetic Phosphonic Acids as Potent Tools to Study Phosphonate Enzymology - Pallitsch, K.; Kalina, T.; Stanković, T. (Synlett, 2019)
Phosphonic acids are highly stable phosphorus-containing compounds, which have been proposed as important intermediates in the global phosphorus cycle. Biogenic phosphonates as well as their synthetic analogues play an important role as potential enzyme inhibitor drugs and as alternative phosphorus source for microbes. Despite these properties, their metabolism is still poorly understood. New degradative pathways and unknown compounds are identified at fast pace. However, most of these pathways include a variety of unique enzymatic transformations, which are difficult to characterize – especially without sufficient amounts of the potential substrates and intermediates of the postulated transformations in hands. Thus, there is a great need for the development of synthetic methodologies to access phosphonic acids in high yields and in enantiomerically pure form for the use in enzymatic studies and in studies on the biological activity of newly isolated natural products, which are often only obtained in low yields. In this Synpacts article we aim at highlighting our recent contributions to this field.1 Introduction2 Phosphonates as Alternative Phosphorus Source3 The Application of Phosphonates in Enzymatic Studies4 Conclusion
Keywords: phosphonate; phosphonic acid; biodegradation; biosynthesis; P–C bond cleavage; enzyme mechanism elucidation; enzyme inhibitors